НЕОБХІДНІСТЬ ЗАСТОСУВАННЯ ЗАСОБІВ ІНТЕРАКТИВНИХ ТЕХНОЛОГІЙ НАВЧАННЯ ІІРИ ФОРМУВАННІ КРИТИЧНОГО МИСЛЕННЯ ЕКОНОМІСТІВ (Педагогіка вищої та середньої школи, 2008)
It is the Article. An author is examine the aspects of forming of critical thought of economists on the basis of component-structural analysis of concept by recomm endations.